New insights into bacterial cellulose materials: production and modification strategies - Horue, Manuel (2018)
Komagataeibacter xylinus cultures produced a high amount of bacterial cellulose (BC), which structure consists in a nanoporous network of interlaced fibers. When the culture is performed under static experimental conditions, a membrane with characteristics of highly hydrated hydrogel and good mechanical properties is obtained with promissory applications in the biomedical field. Bacterial cellulose films can be used for many application such as dermal dressing, scaffolds for tissue regeneration and even as a controlled drug release system. Besides, stirred cultures of K. xylinus produced amorphous cellulose structuresdispersed in the medium with physical and mechanical characteristics different from the membrane. In addition, new properties of BC can be obtained or added if the hydrogel is mixed with other compounds or modified post-purification using both organic and inorganic compounds.